2021
DOI: 10.48550/arxiv.2105.04590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the Milky Way spiral arms from open clusters in Gaia EDR3

A. Castro-Ginard,
P. J. McMillan,
X. Luri
et al.

Abstract: Context. The physical processes driving the formation of Galactic spiral arms are still under debate. Studies using open clusters favour the description of the Milky Way spiral arms as long-lived structures following the classical density wave theory. Current studies comparing the Gaia DR2 field stars kinematic information of the Solar neighbourhood to simulations, find a better agreement with short-lived arms with a transient behaviour. Aims. Our aim is to provide an observational, data-driven view of the Mil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…As far as we know, neither the spiral pattern speed for the MW is well established over the full extent of the disk, nor the assumption that it rotates as a rigid-body has been definitely proven (for a detailed discussion, see Dobbs & Baba 2014;Pettitt et al 2020). Recently, based on the current positions and computed birthplaces of the most complete catalogue of Milky Way open clusters with Gaia EDR3 astrometry, Castro-Ginard et al (2021) found that different spiral arms have distinct angular velocities, nearly co-rotating with the disk and disfavouring the density wave scenario. The understanding of the spiral structure of our Galaxy and the mechanisms involved in its formation are not yet settled.…”
Section: Tentative Birthplaces Of Classical Cepheids Assuming a Rigid...mentioning
confidence: 99%
“…As far as we know, neither the spiral pattern speed for the MW is well established over the full extent of the disk, nor the assumption that it rotates as a rigid-body has been definitely proven (for a detailed discussion, see Dobbs & Baba 2014;Pettitt et al 2020). Recently, based on the current positions and computed birthplaces of the most complete catalogue of Milky Way open clusters with Gaia EDR3 astrometry, Castro-Ginard et al (2021) found that different spiral arms have distinct angular velocities, nearly co-rotating with the disk and disfavouring the density wave scenario. The understanding of the spiral structure of our Galaxy and the mechanisms involved in its formation are not yet settled.…”
Section: Tentative Birthplaces Of Classical Cepheids Assuming a Rigid...mentioning
confidence: 99%
“…the Local arm) suggests that the the MW spiral arms are quite complex with many authors favouring the scenario of flocculent transient spiral structures (e.g. Quillen 2002;Quillen et al 2018;Castro-Ginard et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Dias & Lépine (2005) found how young open clusters must be to trace spiral arms; finding that clusters with ages under ∼ 12 Myr are still located inside the spiral arms. More recently, Castro-Ginard et al (2021) detected overdensities of open clusters younger than 30 Myr and traced the spiral arms with an increased range in Galactic azimuth. Georgelin & Georgelin (1976) were the first to propose the existence of four major spiral arms in the MW based on their determinations of the positions of H ii regions and exciting stars.…”
Section: Introductionmentioning
confidence: 99%